Absolute and ordinary Köthe-Toeplitz duals of some generalized sets of difference sequences - Bektas, Cigdem Asma (My University, 2004)
In this paper we determine the ordinary Kothe-Toeplitz duals of the sets ?ml?(p)?mc(p) and the absolute Köthe-Toeplitz duals of the sets ?mc0(p) and ?mc(p) defined by Et and Basanr [8]. © 2004 by the University of Notre Dame. All rights reserved.
Keywords: Difference sequences; ?-; ?-; ?-duals